GFAPδ/GFAPα ratio directs astrocytoma gene expression towards a more malignant profile - Stassen, Oscar M.J.A. (Oncotarget, 2017)
Astrocytomas are the most common malignant brain tumours and are to date incurable. It is unclear how astrocytomas progress into higher malignant grades. The intermediate filament cytoskeleton is emerging as an important regulator of malignancy in several tumours. The majority of the astrocytomas express the intermediate filament protein Glial Fibrillary Acidic Protein (GFAP). Several GFAP splice variants have been identified and the main variants expressed in human astrocytoma are the GFAPα and GFAPδ isoforms. Here we show a significant downregulation of GFAPα in grade IV astrocytoma compared to grade II and III, resulting in an increased GFAPδ/α ratio. Mimicking this increase in GFAPδ/α ratio in astrocytoma cell lines and comparing the subsequent transcriptomic changes with the changes in the patient tumours, we have identified a set of GFAPδ/α ratio-regulated high-malignant and low-malignant genes. These genes are involved in cell proliferation and protein phosphorylation, and their expression correlated with patient survival. We additionally show that changing the ratio of GFAPδ/α, by targeting GFAP expression, affected expression of high-malignant genes. Our data imply that regulating GFAP expression and splicing are novel therapeutic targets that need to be considered as a treatment for astrocytoma.